Expansive Soil Swelling Test of Small Scale Laboratory Model on Sambungmacan Soil, Central Jawa - Cahyo Agung Saputra; Bambang Setiawan; Yusep Muslih Purwana (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
Soil is one of the most important elements in any civil engineering work, almost all construction activities are related to soil. One of the most common soil problems is expansive soil. This type of soil has a high potential to expand when compared to other types of soil. This research aims to find out how expansive the tested soil is and how it reacts when wetting. The test in this research is experimental, where the expansive soil test is modeled in a rectangular test box with a soil volume of 0.08 m3. The swelling and expansion pressures were measured using proving rings and dials, each totaling five units. The expansive soil used came from Sambungmacan Subdistrict, Sragen Regency, Central Java. The results of the property index test of Sambungmacan soil have a plasticity index percent value of 49.33% and a liquid limit (LL) of 90.16%. The test results showed that the maximum swelling reached 28.3% of the initial soil height of 200 mm and the maximum soil swelling pressure reached 103.23 kPa with a moisture content of 22.62%. The maximum pressure that occurs in each proving ring is at an average moisture content of 31.81%. The results of this study also show the effect of every 1% moisture content will produce a percent soil swelling of 0.40% to 1.08% and the average percentage of swelling pressure that occurs is in the range of 4.65 kPa to 10.26 kPa at every 1% swelling.